Curiosity Factors and English Language Achievements: Non-English Students Department - Asti Gumartifa; Indah Windra Dwie Agustiani; Andriamella Elfarissyah (Universitas Negeri Semarang, 2022)
Curiosity is fundamental in inspiring students to learn English as a foreign language. Their curiosity, on the other hand, does not exist when they are studying English. Students believe that studying English is difficult and implementing speaking skills is even more challenging. This article identifies critical points to recognize students’ curiosity in learning English language as non-English department students’ through a literature reviews. This is a descriptive study, where the researcher finds some supporting theories in term of curiousity in learning English as a foreign language. It relates to the theory that emphasis the difference among students’ curiosity in learning English. Theory and evidence are discussed in the field of psychology and pedagogy, curiosity and education, curiousity in learning, socioeconomic and curiosity. The study's conclusion is that there is no level of socio-economic difference in the curiosity possessed by a student. Curiosity serves intrinsic motivation to learn English language. Consider factors such as learning facilities; language laboratorium, English language atmosphere and environment, partners’ stimulation and feedback on student in practicing English, and socioeconomic status analysis. Therefore, curiosity is as a self-motivation for English language achievement which involves teachers and students. The findings of this study can help educators have a better understanding of how to get children to enjoy English. Teachers can provide attractive learning procedures, materials, and strategies. Students will have a high level of interest as a result of this experience of compassion.